1976
DOI: 10.1080/00039896.1976.10667230
|View full text |Cite
|
Sign up to set email alerts
|

Low-Tar and High-Tar Cigaretters

Abstract: Mice were exposed for 7 to 8 minutes on weekdays to fresh smoke from high-tar (HT) or low-tar (LT) cigarettes for varying periods of up to 36 weeks. Mice exposed to HT cigarettes exhibited more marked alterations in humoral immune responsiveness, hematological profiles, and pulmonary pathologic findings than those exposed to LT cigarettes. However, cell-mediated immune responsiveness to both bacterial and tumor-specific antigens was depressed similarly in animals exposed to HT or LT cigarettes. Furthermore, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1979
1979
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Several studies (45)(46)(47)(48) showed no changes, whereas others (5,13,49,50) showed decreased mitogen-induced T cell proliferation. We reported that nicotine did not affect T cell proliferation induced by anti-CD3/CD28 Abs (19).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies (45)(46)(47)(48) showed no changes, whereas others (5,13,49,50) showed decreased mitogen-induced T cell proliferation. We reported that nicotine did not affect T cell proliferation induced by anti-CD3/CD28 Abs (19).…”
Section: Discussionmentioning
confidence: 99%
“…Nicotine, however, is the only agent considered synonymous with smoking in modulating the immune system (5,12). For example, Holt and colleagues (13) observed that exposure to smoke from high-nicotine cigarettes is more immunosuppressive than the smoke from low-nicotine cigarettes. In experiments separating the vapor phase from the particulate phase, the Sopori group (5) found that particulate phase-containing nicotine is necessary for the immunosuppression associated with cigarette smoke.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There is increasing evidence that nicotine, the primary constituent among the thousands of chemicals in all tobacco products, is an immune modulator having sole effects on host immunity that reflect the effects of cigarette smoke in its entirety [19][20][21]. Although, our understanding of the mechanisms whereby nicotine affects host immunity is largely incomplete, nicotine is being used in medications (e.g., patch, gum, nasal spray/inhaler) to aid smoking cessation [22] and is being considered as an anti-inflammatory agent for the treatment of diseases such as Alzheimer's disease [23], Parkinson's disease [24], and autoimmune diseases [25].…”
Section: Introductionmentioning
confidence: 99%
“…Finklea and colleagues [4] showed that smokers had lower titers and a decreased t 1/2 of antibodies to influenza virus after natural disease and immunization. In addition, Holt’s group [6, 7] reported that the longevity of the immune response to subunit vaccine was severely depressed 50 weeks post-vaccination in smokers. Reduced protection seen in smokers compared with nonsmokers after vaccination is further supported by a study from Winter et al [5] in which it was found that smokers who received hepatitis B vaccines at 0, 1, and 6 months (standard booster vaccine) had lower Ab levels than nonsmokers after 3, 7, and 13 months.…”
Section: Introductionmentioning
confidence: 99%